Virginia Farmers Survey - Patricia Rice; Terry Canup (Journal of Applied Communications, 1986)
Recently, I was on the phone with a commercial farmer regarding a survey on farm financial management tasks; at the end he commented about marketing and now negligent the land-grant universities and extension were in providing marketing training and information.